2019
DOI: 10.23850/22565035.1785
|View full text |Cite
|
Sign up to set email alerts
|

Análisis Del Caudal en Un Disco De Freno Automotriz Con Álabes De Ventilación Tipo Naca 66-209, Utilizando Velocimetría Por Imágenes De Partículas

Abstract: Analysis of the flow on an automotive brake disc with NACA 66-209 type ventilation alabs, using particle image velocimetry Análisis del caudal en un disco de freno automotriz con álabes de ventilación tipo NACA 66-209, utilizando velocimetría por imágenes de partículas

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Finally, it is concluded that the disc with a configuration of 15 profiles is an excellent design option, because it has no blocking effects at low speeds, and in addition, aerodynamics presents and energetically as proposed by [14] [19].…”
Section: Methodsmentioning
confidence: 97%
“…Finally, it is concluded that the disc with a configuration of 15 profiles is an excellent design option, because it has no blocking effects at low speeds, and in addition, aerodynamics presents and energetically as proposed by [14] [19].…”
Section: Methodsmentioning
confidence: 97%
“…These configurations have a more aerodynamic profile compared to the automotive disc brake with the NACA 66-209 type ventilation blades, which makes the airflow inside the ventilation blades circulate with better efficiency, and the rate of heat evacuated higher, thus increasing the efficiency of the disc brake. According to the authors of [22], an increase in the number of blades in the disc brake geometry design does not promote the block effect at low speeds and also provides better performance for heat dissipation. Table 5 presents the most relevant parameters and dimensions of the proposed brake discs.…”
Section: Proposal For a New Disc Brake Geometrymentioning
confidence: 99%
“…On the other hand, García-León et al [22] proposed a new geometric arrangement to improve airflow in a vehicular disc brake, considering the ventilation blades based on NACA 66-209 type aerodynamic profiles. To validate this design proposal, they constructed a 1:1 prototype with the aid of additive manufacturing.…”
Section: Introductionmentioning
confidence: 99%
“…The N-38 type ventilation blade geometry improves heat dissipation during the braking process is proposed after analyzing the previous results in other studies. According to [13], an increase in the number of blades on the disc brake geometry with the block effect design does not promote low speed and provides better performance on the heat dissipation. Figure 1 shows the disc brake used: (a) 3D view, (b) transparent view, and (c) blade geometry.…”
Section: Disc Brake Geometrymentioning
confidence: 99%
“…On the other hand, García-León et al [13] proposed a new geometric arrangement to improve airflow in a common vehicular disc brake, considering the ventilation blades based on NACA 66-209 type aerodynamic profiles; this purpose was used particle image velocimetry (PIV) technique. The results indicate that a configuration of 20 blades improves heat dissipation [14,15].…”
Section: Introductionmentioning
confidence: 99%